2002
DOI: 10.1530/eje.0.1460607
|View full text |Cite
|
Sign up to set email alerts
|

Increased adipose tissue secretion of interleukin-6, but not of leptin, plasminogen activator inhibitor-1 or tumour necrosis factor alpha, in Graves' hyperthyroidism

Abstract: Objective: This study was designed to investigate adipose tissue secretion of interleukin-6 (IL-6), leptin, tumour necrosis factor alpha (TNF-a) and plasminogen activator inhibitor-1 (PAI-1) in Graves' hyperthyroidism. Design: We studied 10 patients before and during (after 8 weeks) anti-thyroid treatment for Graves' hyperthyroidism and 16 healthy, euthyroid control subjects. Methods: Plasma levels of thyroid hormones and serum/plasma levels of IL-6, leptin, TNF-a and PAI-1 were analysed. Subcutaneous fat biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 33 publications
3
25
0
3
Order By: Relevance
“…For instance, cytokine levels are elevated in thyroid tissue from patients with active disease (64,65). Wahrenberg et al (24) have reported that adipose tissues from these individuals release several-fold higher levels of IL-6 than do similar tissues from control subjects. Circulating IL-6 levels have also been found to be elevated in Graves' disease (17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For instance, cytokine levels are elevated in thyroid tissue from patients with active disease (64,65). Wahrenberg et al (24) have reported that adipose tissues from these individuals release several-fold higher levels of IL-6 than do similar tissues from control subjects. Circulating IL-6 levels have also been found to be elevated in Graves' disease (17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 93%
“…Its expression can be enhanced substantially in differentiated 3T3F442A adipocytes by ␤-adrenergic activation, an effect also seen in cultures derived from s.c. breast tissue and abdominal wall (43,44). The finding that IL-6 mRNA levels correlate positively with tissue volumes in TAO (23) suggests that a promotion by IL-6 of adipogenesis could underlie the expansion of orbital fat in TAO (1,24).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In patients with GD, IL-6 is produced by infiltrating immune cells and thyrocytes (25). Serum IL-6 levels in patients with GD have been reported to be significantly higher than those in healthy controls (21,26). However, the clinical significance of serum IL-6 levels remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have described an increase in serum PAI-1 concentration in hyperthyroidism, whereas others did not detect any differences (7)(8)(9).…”
Section: Introductionmentioning
confidence: 89%